2022
DOI: 10.1097/mao.0000000000003731
|View full text |Cite
|
Sign up to set email alerts
|

One Click Is Not Enough: Anatomy-Based Fitting in Experienced Cochlear Implant Users

Abstract: ObjectiveTo evaluate a new methodological approach of applying anatomy-based fitting (ABF) in experienced cochlear implant (CI) users.ParticipantsThree experienced unilateral and bilateral CI users with postlingual hearing loss.InterventionPostoperative imaging, via a high-volume Dyna computed tomography, and exact electrode measurement positions were integrated into the clinical fitting software following a new procedure, which adapted individual frequency bandwidths within the audio processor.Main Outcome Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 9 publications
(10 reference statements)
0
10
0
1
Order By: Relevance
“…Either immediately to verify the surgical outcome ( O’Connell et al 2016 ; Rathgeb et al 2019 ) or later in the follow-up to monitor electrode migration ( Dietz et al 2016 ) or to explain parts of the variability in postoperative speech understanding outcomes ( Chakravorti et al 2019 ). In addition, CI audio processor fitting can be personalized to take into account patient anatomy and electrode locations, potentially improving hearing outcomes ( Venail et al 2015 ; Kurz et al 2022 ; Mertens et al 2022 ). The current gold standard for determining intracochlear electrode positions is radiography, which entails radiation exposure, requires dedicated infrastructure, and incurs additional costs, limiting its use in routine clinical practice ( McCollough et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Either immediately to verify the surgical outcome ( O’Connell et al 2016 ; Rathgeb et al 2019 ) or later in the follow-up to monitor electrode migration ( Dietz et al 2016 ) or to explain parts of the variability in postoperative speech understanding outcomes ( Chakravorti et al 2019 ). In addition, CI audio processor fitting can be personalized to take into account patient anatomy and electrode locations, potentially improving hearing outcomes ( Venail et al 2015 ; Kurz et al 2022 ; Mertens et al 2022 ). The current gold standard for determining intracochlear electrode positions is radiography, which entails radiation exposure, requires dedicated infrastructure, and incurs additional costs, limiting its use in routine clinical practice ( McCollough et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, when using the approach of an individualized CC, an accurate prediction of AID before CI surgery is needed (4,7,9). However, apart from the individual cochlear morphology, the AID may be influenced by the electrode array length, the array design (lateral wall vs. perimodiolar), and the surgical approach (round window approach vs. cochleostomy) (28). van der Marel et al (29) showed that more than 81% of the variances in postoperative insertion depths can be explained by the interaction of CDL and surgical insertion.…”
Section: Discussionmentioning
confidence: 99%
“…An association between deeper insertion and frequency discrimination is frequently discussed ( 58 60 ). According to Peters et al, the pitch perception with a CI is 1 to 2 octaves lower than the predicted pitch.…”
Section: Discussionmentioning
confidence: 99%